Evaluating kariah leadership and impact to mosque management: Case study in Kedah - Azfahanee, Zakaria (2021)
A mosque has always been a place for Muslims to gather either for both social and religious purposes. During the days of Prophet Muhammad (p.b.u.h) the mosque has always been a one stop center for Muslims. Formerly, mosques commonly served as an administrative center, hospital, school and entrepreneurship hub. However, the scenario has changed and the mosque management in Malaysia has been criticized for their incompetence in managing the mosque. Therefore, the aim of this study is twofold. First, this study aims to evaluate the effectiveness of leader’s competence, delivery effectiveness & knowledge transfer. Second, this study evaluates the leaders’ understanding of their respective roles. This study utilizes a qualitative research approach. 16 respondents consist of 12 mosque officers, three officials of Islamic Religious Center (IRC) and one official of Kedah Islamic Affairs Department (KIAD) were interviewed and shared their insights on their daily activities and challenges they faced during their service. In addition, observation and document review were also conducted and data were analyzed using the hermeneutic approach. From the analysis, it shows that the competencies required are managing skills, ability to make decisions, communication skills and ability to reduce and manage conflicts. Leaders also need to have the ability to use technology as to accelerate the process of knowledge transfer. Besides, the Imam of the mosque holds two main positions in the community, Imam as well as chairman of the mosque committee respectively. Additionally, it was discovered that there are remarkable numbers of mosque leaders who are above 60 years of age whereby succession planning is not being practiced. The evaluation measures for the mosque management does not include the evaluation of leaders in detail. For instance, no formal listing or documentation is provided in regards to the status of the active and inactive mosques. Overall, the result obtained from the study could be useful to assist the mosque management committee and KIAD to strategize ways to improve the management of the mosque. It could also serve as a stepping stone for the government to introduce a new policy for the betterment of the mosque and Muslim community as a whole.